Paradigm Dual-Role Energy: Synergy Management Energy and Defense For Sustainable National Resilience - Mia Kusmiati (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Purpose – Purpose This is for explore interconnection strategic between system energy and defense in support resilience national with propose draft paradigm energy dual role paradigm This positioning energy No only as protected objects​ from threat external, but also as subject strategic support​ operation military through energy renewable, implementation network smart, and technology storage battery. Design/ methodology / approach – Research This use approach review library systematic (SLR) for synthesize findings academic and reports policy from three year lastly, which involves source journal national (SINTA indexed) and international (Elsevier, Springer, IEEE, etc.), with focus on intersection between resilience energy and defense strategy national. Findings – Review This disclose that infrastructure resilient energy​ increase capability defense, while system formidable defense​ ensure continuity supply energy national research​ This propose an integrative model consisting of from three layer strategic: integration policy national (between RUEN and RENSTRAHAN), development infrastructure green and digital, and development capacity source Power man together. Framework Work integrative This strengthen reciprocal resilience​ between sector energy and defense. Implications practical – The makers policies, institutions military, and stakeholders interest energy pushed for together implementing synchronized strategies, integration curriculum and investment in infrastructure digital energy use reach resilience national term long in face uncertainty geopolitics and environment. Originality / Value – Study This introduce framework Work new paradigm energy role double in defense national, which provides runway theoretical and practical for integrate transition energy sustainable with planning defense strategic. Study This contribute in a way conceptual for bridge gap between policy energy and defense strategy, especially in context threat hybrids and vulnerabilities system cyber-physical.